Brain and Retinal Abnormalities in the 5xFAD Mouse Model of Alzheimer's Disease at Early Stages - Zhang, Mengrong; Zhong, Liting; Han, Xiu; Xiong, Guoyin; Xu, Di; Zhang, Sensen; Cheng, Haiyang; Chiu, Kin; Xu, Ying (Frontiers in Neuroscience, 2021)
One of the major challenges in treating Alzheimer’s Disease (AD) is its early diagnosis. Increasing data from clinical and animal research indicate that the retina may facilitate an early diagnosis of AD. However, a previous study on the 5xFAD (a fast AD model), showing retinal changes before those in the brain, has been questioned because of the involvement of the retinal degeneration allele Pde6brd1. Here, we tested in parallel, at 4 and 6 months of age, both the retinal and the brain structure and function in a 5xFAD mouse line that carries no mutations of rd1. In the three tested regions of the 5xFAD brain (hippocampus, visual cortex and olfactory bulb), the Abeta plaques were more numerous than in WT littermates already at 4M, but deterioration in the cognitive behavioral test and LTP lagged behind, showing significant deterioration only at 6M. Similarly in retina, structural changes preceded functional decay. At 4M, the retina was generally normal except for a thicker outer nuclear layer in the middle region than WT. At 6M, the visual behavior (as seen by an optomotor test) was clearly impaired. And while the full-field and pattern ERG responses were relatively normal, the light responses of the retinal ganglion cells (measured with multi-electrode-array recording) were decreased. Structurally, the retina became abnormally thick with few but more Abeta plaques, and activated glia cells. In conclusion, the time line of the degenerative processes in the retina and the brain is similar, supporting the use of non-invasive methods to test the retinal structure and function to reflect changes in the brain for early AD diagnosis.